Temporal dynamics of pitch in human auditory cortex - Gutschalk, Alexander; Patterson, Roy D.; Scherg, Michael; Uppenkamp, Stefan; Rupp, André (NeuroImage, 2004)
Recent functional imaging studies have shown that sounds with temporal pitch produce selective activation in anterolateral Heschl's gyrus. This paper reports a magnetoencephalographic (MEG) study of the temporal dynamics of this activation. The cortical response specific to pitch was isolated from the intensity-related response in Planum temporale using a ‘continuous stimulation’ paradigm in which regular and irregular click trains alternate without interruption. The mean interclick interval (ICI) was 6, 12, 24, or 48 ms; the train length was 720 ms. The auditory sustained field serves as a level-dependent baseline that enhances the signal-to-noise ratio over previous techniques. The onset of pitch was accompanied by a prominent transient field, followed by a strong sustained field, both of which were associated with sources in lateral Heschl's gyrus. The sustained field rose from baseline about 70 ms after the onset of temporal regularity, asymptoted at about 450 ms, and commenced its return to baseline about 70 ms after pitch offset. The peak of the transient field occurred between 130 and 190 ms after regularity onset depending on the ICI. The latencies of the cortical pitch response are substantially longer than might be anticipated from temporal models of pitch perception. This finding suggests that the temporal integration associated with periodicity processing occurs in a subcortical structure, and that the cortical responses reflect subsequent processes involving the measurement of pitch values and changes in pitch.